Bat population recoveries give insight into clustering strategies during hibernation - Natália Martínková; Stuart J. E. Baird; Vlastislav Káňa; Jan Zima (Frontiers in Zoology, 2020)
Abstract Background Behaviour during hibernation contributes to energy conservation in winter. Hibernating bats select roosts with respect to physiological and environmental stressors, available local microclimate and species-specific requirements. Results We found that, in the period between 1977 and 2018, hibernating Myotis myotis and Rhinolophus hipposideros bats showed exponential population growth. The growth rates, corrected for local winter seasonal severity and winter duration, were equal to 10 and 13%, respectively. While R. hipposideros only utilised the thermally stable and, at survey time, warmer corridors in the hibernaculum, an increasing proportion of M. myotis roosted in the thermally stable corridors as their abundance increased. About 14% of all hibernating M. myotis displayed solitary roosting, irrespective of other covariates. Those bats that clustered together formed progressively larger clusters with increasing abundance, particularly in cold corridors. We found no statistically significant relationship for clustering behaviour or cluster size with winter severity or winter duration. Conclusions Abundance of hibernating bats is increasing in Central Europe. As the number of M. myotis bats increases, thermally unstable corridors become saturated with large clusters and the animals begin to roost deeper underground.